COREOGRAPHY AND STAGE ADAPTATION - FORMS OF STAGE PRESENTATION OF THE FOLK DANCE TRADITION (COMPARATIVE ANALYSIS) - Kostov, Stojance (PALIMPSEST / ПАЛИМПСЕСТ, 2018)
The folk dance tradition in the folklore ensembles in Macedonia is presented in different ways. Every artistic leader, demonstrator or choreographer of these ensembles gives its own mark in shaping it. In this text, the comparative analysis of choreography and stage adaptation as forms of a stage - artistic presentation of the folk dance tradition will be made.